Climate change and indigenous peoples : the search for legal remedies - Abate, Randall; Kronk, Elizabeth Ann (Edward Elgar, 2013)
"Indigenous peoples occupy a unique niche within the climate justice movement, as many indigenous communities live subsistence lifestyles that are severely disrupted by the effects of climate change. Additionally, in many parts of the world, domestic law is applied differently to indigenous peoples than it is to their non-indigenous peers, further complicating the quest for legal remedies. The contributors to this book bring a range of expert legal perspectives to this complex discussion, offering both a comprehensive explanation of climate change-related problems faced by indigenous communities and a breakdown of various real world attempts to devise workable legal solutions. Regions covered include North and South America (Brazil, Canada, the US and the Arctic), the Pacific Islands (Fiji, Tuvalu and the Federated States of Micronesia), Australia and New Zealand, Asia (China and Nepal) and Africa (Kenya)."--pub. desc